2013
DOI: 10.1186/1751-0473-8-16
|View full text |Cite
|
Sign up to set email alerts
|

CellSegm - a MATLAB toolbox for high-throughput 3D cell segmentation

Abstract: The application of fluorescence microscopy in cell biology often generates a huge amount of imaging data. Automated whole cell segmentation of such data enables the detection and analysis of individual cells, where a manual delineation is often time consuming, or practically not feasible. Furthermore, compared to manual analysis, automation normally has a higher degree of reproducibility. CellSegm, the software presented in this work, is a Matlab based command line software toolbox providing an automated whole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
86
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 25 publications
0
86
0
Order By: Relevance
“…Mouse nuclei segmentation: Processing and segmentation of mouse nuclei is performed using the MATLAB toolbox called "CellSegm" 69 . The toolbox provides the user with several input options for smoothing (coherence enhancing diffusion, edge enhancing diffusion, gaussian) and thresholding (iterative thresholding, adaptive thresholding, gradient thresholding, ridge enhancement).…”
Section: Generation Of Reference Emission Spectral Profilesmentioning
confidence: 99%
“…Mouse nuclei segmentation: Processing and segmentation of mouse nuclei is performed using the MATLAB toolbox called "CellSegm" 69 . The toolbox provides the user with several input options for smoothing (coherence enhancing diffusion, edge enhancing diffusion, gaussian) and thresholding (iterative thresholding, adaptive thresholding, gradient thresholding, ridge enhancement).…”
Section: Generation Of Reference Emission Spectral Profilesmentioning
confidence: 99%
“…It has taken the community many decades and great endeavor to segment, identify, and analyze cells for explaining the cellular and molecular processes of health and disease. Studies have showed that cell segmentation can contribute to the better cell recognition in various fields of cell biology (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) and great advances have been achieved. However, it still has a long way to go before meeting the ultimate goal that the developed method can segment and identify different types of cells autonomously and the biologists can trust the segmentation and identification results blindly.…”
Section: The Future Of Cell Segmentationmentioning
confidence: 99%
“…However, most state‐of‐the‐art methods or software tools mainly rely on existing basic image processing algorithms developed many decades ago. For example, the watershed algorithm is adopted by Cellsegm , SMASH , ImageJ , CellProfiler , Alanazi's method , and the recently reported method by Tsujikawa et al (CYTOA 95:4; pp 389–398). Classical thresholding is adopted by Cellsegm, SMASH, ImageJ, and Alanazi's method while K ‐means clustering is adopted by Tsujikawa's method.…”
mentioning
confidence: 99%
“…Recently developed multiplexed fluorescence in-situ hybridization (mFISH) (Chen et al, 2015;Codeluppi et al, 2018;Lubeck et al, 2014) and in situ mRNA tissue sequencing (Ke et al, 2013;Lee et al, 2015;Maniatis et al, 2019;Ståhl et al, 2016;Vickovic et al, 2019a;Wang et al, 2018) techniques have enabled the simultaneous measurement of multiple mRNAs in a spatial context. Application of cell segmentation algorithms to images obtained by these techniques identifies cells, and allows classification of classes or types of cells together with their locations (Hodneland et al, 2013;Jiang et al, 2019;Kong et al, 2015;Salvi et al, 2019). The rapid increase in establishment of in situ transcriptomics platforms inspired the inception of the SpaceTx Consortium (Perkel, 2019), which aims to systematically evaluate these platforms and protocols.…”
Section: Introductionmentioning
confidence: 99%